A longitudinal follow-up study of people with Prader–Willi syndrome with psychosis and those at increased risk of developing psychosis due to genetic subtype. Issue 11 (August 2014) - Larson, F. V.; Whittington, J.; Webb, T.; Holland, A. J.
<x content-type="archive" xml:space="preserve">Abstract</x> Background People with Prader–Willi syndrome (PWS), a genetically defined developmental disorder, are at increased risk of developing psychotic illness. This is particularly the case for those with a genetic subtype of PWS called maternal uniparental disomy (mUPD), where rates of psychosis are more than 60% by early adult life. Little is known about the long-term course of their disorder. Method Individuals who had had episodes of psychosis or were at increased risk of developing psychosis due to their genetic subtype and had taken part in a previous study were contacted. Ten people were untraceable or deceased, leaving a total of 38 potential participants. Of these, 28 agreed to take part in a follow-up interview or complete a questionnaire about their mental health and medication. This represented 20/35 (57.1%) people from the original study who had had psychosis and 8/13 (61.5%) people who were at risk due to their genetic subtype. They were thought to be representative of those groups as a whole based on IQ and number of episodes of psychosis. Results Two individuals had had recurrent episodes of psychosis while all others remained well. There were no new-onset cases of psychosis in those at risk. Individuals with PWS remained on high levels of psychiatric medication throughout the follow-up period. Conclusions Recurrent episodes of psychosis may be rare in people with PWS once stability has been achieved in the management of their illness. We speculate that this may be due to the protective influence of medication.